Implementation of E-Office at the Office of the Regional Development Planning Agency for Research and Development of Riau Province - Nursavinah, Nursavinah; Afandi, Syed Agung (Literacy: Journal of Education and Social Science, 2024)
Indonesia has experienced a shift towards a state system better known as bureaucratic reform. This reform includes plans to implement electronic government (e-government) in the public sector. This research aims to analyze the implementation of E-Office program policies in supporting E-government within the Riau Province government. The author uses a qualitative descriptive analysis method by collecting data through in-depth interviews, observation and documentation. The theory used is Grindle's theory of policy implementation. Based on the research results, it shows that the implementation of e-Office to support E-government measures in the Riau Province Bappedalitbang work environment generally has a positive impact on employees, namely on the type of benefits indicator. The presence of e-office makes it easier for employees to send or check manuscripts. services that are required. However, it cannot be denied that there are still indicators that have not been implemented well, namely the Resources Commitment because there are still infrastructure that is still not optimal. Because there is a significant shortage of facilities and infrastructure to support the implementation of e-Office, such as scanners and PC computers, which hinder the effective implementation of e-Office. Apart from that, the indicator for program implementers is that there are still employees who are unfamiliar with technological changes even though training and introduction to e-Office have been carried out.